Active Packaging Films from Ethylene Vinyl Alcohol Copolymer and Clove Essential Oil as Shelf Life Extenders for Grass Carp Slice. Issue 7 (28th April 2016) - Yang, Hui; Wang, Jing; Yang, Fuxin; Chen, Mo; Zhou, Dongxiang; Li, Li
Abstract : Active packaging provides a way to prevent the food putrefaction effectively. Various studies provide information on the actual preservation effect of active packaging or the migration of active agents from active films into various food stimulants separately. However, there is little related data available regarding the combined analysis of release and preservation effect. In this work, we examined the properties of active food packaging films successfully produced by extrusion of ethylene vinyl alcohol copolymer (EVOH) films with clove essential oil (C). The characterization of mechanical, thermal and barrier properties of the packaging polymers film showed that the addition of clove essential oil did not decrease their properties and C as plasticizer improved process fluidity of EVOH resin. The release of C from film to various food stimulants was measured by using HPLC, and Fickian diffusion models were used to fit the data with appropriate equation. The effects of E/C (ethylene vinyl alcohol copolymer/clove essential oil) films on quality assessment of Grass Carp slice based on sensory analysis and biochemical indices during refrigerated storage (4 ± 1°C) were examined over the period of 10 days. Total volatile basic nitrogen (TVB‐N), total viable counts, pH, TBA, water holding capacity (WHC) and texture properties were evaluated. The results indicated that the active film containing 3% clove essential oil had different release parameters in four food stimulants and it could effectively maintain the fish freshness and extend the shelf life to 7–8 days during cold storage compared with control group, which was only 4 days. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The active film obtained by adding 3% clove essential oil to EVOH copolymers could be used in the design of antioxidant active packaging for aqueous, acidic and alcoholic food products.